BIL1-mediated MP phosphorylation integrates PXY and cytokinin signalling in secondary growth - Han, Soeun; Qi, Jiyan; Greb, Thomas (Nature plants, 2018)
The vascular cambium is a lateral meristem that is particularly active during secondary growth. Here, several signalling pathways (peptide, receptor, auxin and cytokinin) are linked together to explain how vascular development is regulated.
Gesehen am 21.08.2019